THE USE OF POSSE STRATEGY TO DEVELOP READING COMPREHENSION OF THE EIGHTH GRADE STUDENTS OF SMP NEGERI 1 TORIBULU - Yani, Riska; Munir, Syahrul; Lebagi, Desrin (Universitas Muhammadiyah Makassar, 2025)
The objective of the study was to determine the efficacy of the POSSE (Predict, Organize, Search, Summarize, and Evaluate) Strategy in enhancing students' reading comprehension. This study was carried out at the SMP Negeri 1 Toribulu. The research population comprised 66 eighth-grade students. The research used quantitative research, particularly in Quasi-Experimental Design. To get the sample, the researcher employed cluster random sampling. The data was collected using exam items, which included 10 multiple-choice and 5 essay questions. There were pretest and posttest in both groups, and the experimental group received treatment while the control group did not. The results showed the students' mean score of the experimental group (55.64) on the posttest was higher than the score from the control group (31.24) on the posttest. The sig value is calculated using statistical results. With a 2 tailed of 0.0000.05, it can be determined that there is a significant difference in the mean score of pupils' learning outcomes between the POSSE-based learning model and the usual method taught by the teacher.